Renal involvement in various pediatric liver diseases : Review of literature and report on tyrosinemia cases - Mona Mohammed Habeeb Allah; Ahmed Mohammad Badr; Hanaa Mostafa Elkaraksy; Neveen Abdelmonem Soliman (Cairo : Mona Mohammed Habeeb Allah, 2010)
Heraeditary tyrosinemia type p1 (B(HTp1 (B) is an increasingly recognized inborn error of metabolism among Egyptian children . To define the presenting clinical biochemical and imaging features the outcome of NTBC therapy and liver transplantation in a cohort of Egyptian children diagnosed with HTp1 (B. The study was carried out at the Pediatric Hepatology Unit at Cairo University , Children's Hospitals
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Hepatorenal tyrosinemia; Heraeditary tyrosinemia type p1 s; Tyrosinemia